Corrosion-resistant alloy reinforcing bar and its manufacturing method
Patent Information
- Application Number
- JP2024550611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-01-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-01-18
AI Technical Summary
【0017】 本願の技術的解決手段は、以下の利点を有する。
Smart Images

Figure 2025506561000001 
Figure 2025506561000002 
Figure 2025506561000003
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to a Chinese patent application bearing application number 202210708417.8 and entitled "Corrosion-resistant alloy rebar and manufacturing method thereof" filed with the China Patent Office on June 22, 2022, the entire contents of which are incorporated herein by reference. [Technical field]
[0002] This application relates to the technical field of reinforcing bars, and in particular to corrosion resistant alloy reinforcing bars and methods of making same. [Background technology]
[0003] Reinforced concrete structures are the most important structures, but their lack of durability has become a major challenge in the industry. Corrosion-resistant alloy rebars combine the appearance, mechanical properties, workability and corrosion resistance of ordinary rebars, and are an important means of solving the problem of the lack of durability of reinforced concrete structures. However, there are still some issues with the existing corrosion-resistant alloy rebars, making it difficult to fully promote their use.
[0004] For example, Patent CN112375995A discloses a 400MPa grade corrosion-resistant rebar and its production method, the components of the 400MPa grade corrosion-resistant rebar are Cr: 9.5-10.4% by mass, Mo: 1.0-1.2% by mass, Mn: 0.3-0.6% by mass, Ni: 0.01-1% by mass, Cu: 0.01-0.5% by mass, C≦0.014% by mass, N≦0.004% by mass, Nb: 0.01-0.05% by mass, Si: 0.2-0.6% by mass, and the balance is Fe and unavoidable impurities. The microstructure of the corrosion-resistant rebar is bainite and ferrite, and it belongs to the ultra-low carbon high alloy corrosion-resistant rebar, and has excellent mechanical properties and corrosion resistance.
[0005] However, since the Cr and Mo contents in the above corrosion-resistant rebar alloy elements are high, the production cost is high, and the use of the corrosion-resistant rebar is greatly restricted. Summary of the Invention [Problem to be solved by the invention]
[0006] The technical problem to be solved by this application is to overcome the deficiencies of the prior art, that is, the high content of Cr and Mo in the alloy elements of corrosion-resistant rebars results in high production costs, which greatly limits the use of the corrosion-resistant rebars. [Means for solving the problem]
[0007] For this reason, the present application provides a corrosion-resistant alloy rebar, comprising: 0.05-0.25% by weight of C, 1.05-2% by weight of Si, 0.3-1.5% by weight of Mn, 0.5-2.5% by weight of Cr, 0.05-1% by weight of Ni, 0.001-0.005% by weight of O, 0.001-0.0035% by weight of S, 0.005-0.1% by weight of Ti, 0.005-0.1% by weight of Al, 0.005-0.03% by weight of V, 0.005-0.03% by weight of Nb, and the remainder being Fe and unavoidable impurities; The Si and Mn contents satisfy 2≦Si / Mn≦5, the Si and Cr contents satisfy 0.75≦Si / Cr≦1.5, and the Ti and Al contents satisfy 0.02 wt %≦Ti+Al≦0.2 wt %.
[0008] Optionally, the Si is 1.2-1.8%, And / or, the Mn content is 0.4 to 1%, And / or, the Cr content is 0.85 to 2%.
[0009] Optionally, the Si is 1.35 to 1.65%, And / or, the Mn content is 0.45 to 0.75%, And / or, the Cr content is 1.35 to 1.75%.
[0010] Optionally, the C is 0.05 to 0.15%.
[0011] Optionally, the C is 0.07 to 0.12%.
[0012] Optionally, the Ti is 0.01 to 0.075%, And / or, the Al content is 0.01 to 0.075%.
[0013] The present application also provides a method for producing said corrosion-resistant alloy rebar, comprising the steps of smelting, refining, continuous casting, rolling and cooling, which are carried out in sequence.
[0014] Optionally, the raw materials for manufacturing the corrosion-resistant alloy rebar include ferrosilicon alloy and silicon manganese alloy, and the mass ratio of the ferrosilicon alloy to the silicon manganese alloy is (2-5):1.
[0015] Optionally, in the continuous casting step, a drawing speed is 2.5 to 3.5 m / min; And / or, in the cooling step, the temperature of the reinforcing bar transferred to the cooling bed is 820°C to 1000°C; And / or, the rolling step includes a step of heating the continuous cast billet and performing rough rolling and finish rolling.
[0016] Optionally, the temperature for heating the continuous cast billet is 1150-1250°C, the rough rolling temperature is 1000-1120°C, and the finish rolling temperature is 1000°C or higher. Effect of the Invention
[0017] The technical solution of the present application has the following advantages:
[0018] 1. In the corrosion-resistant alloy rebar according to the present application, Si, Mn, Cr, Al, and Ti in the prescription of the present application are comprehensively designed, and the decrease in corrosion resistance caused by the decrease in Cr content is compensated for by elements such as Si, Ti, Al, and Mn. Therefore, even when the Mo element is not mixed into the prescription and the Cr element content is significantly reduced, a corrosion-resistant alloy rebar with excellent mechanical properties and corrosion resistance can be obtained, and the production cost of the corrosion-resistant alloy rebar can be significantly reduced.
[0019] 2. The corrosion-resistant alloy rebar according to the present application not only realizes excellent corrosion resistance of the corrosion-resistant alloy rebar based on the chemical composition design of the present application, but also has excellent mechanical properties, low production costs, and is suitable for practical production and processing.
[0020] 3. The corrosion-resistant alloy rebar according to the present application is based on the chemical composition design scheme of the present application, and by combining it with the smelting technology and the controlled rolling / controlled cooling process in the manufacturing method, it is ensured that the strengthening effect of the alloying elements is exerted and that a ferrite + pearlite multiphase structure is obtained, thereby ensuring the corrosion resistance and mechanical properties of the corrosion-resistant alloy rebar, while also reducing the difficulty and cost of production. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The following examples are provided for a better understanding of the present application, and are not limited to the above-mentioned best embodiment, and are not intended to limit the content and scope of protection of the present application. Any products that are the same or similar to those of the present application and are obtained by combining the suggestions of the present application or the features of the present application with other prior art will fall within the scope of protection of the present application.
[0022] Unless specific experimental procedures or conditions are specified in the examples, they may be carried out according to the operations or conditions of the general experimental procedures described in the literature in the field. The manufacturers of the reagents or instruments used are not specified, and all are general reagent products available commercially.
[0023] The ferrosilicon alloy in this application has a particle size of 10 to 30 mm, and its main components are Si: 75 wt%, S: 0.002 wt%, C: 0.01 wt%, Al: 0.1 wt%, Ti: 0.01 wt%, P: 0.02 wt%, and the remainder are iron and impurities. It was purchased from Qinghai Baitong High-purity Materials Co., Ltd.
[0024] The silicon manganese alloy in this application has a particle size of 10 to 30 mm, and its main components are Mn: 83 wt%, Si: 1.94 wt%, C: 0.65 wt%, P: 0.15 wt%, S: 0.005 wt%, and the remainder are iron and impurities. It was purchased from Ningxia Yitong Industrial Co., Ltd.
[0025] The ferrochrome alloy in this application has a particle size of 30 to 50 mm, and its main components are Cr: 60 wt%, Si: 0.87 wt%, C: 0.14 wt%, S: 0.002 wt%, P: 0.034 wt%, and the remainder are iron and impurities. It was purchased from Tianjin Haoyuan Metal Materials Co., Ltd.
[0026] The ferro-titanium alloy in this application has a particle size of 10 to 30 mm, and its main components are Si: 1.85 wt%, S: 0.014 wt%, C: 0.04 wt%, Al: 1.35 wt%, Ti: 32.94 wt%, P: 0.042 wt%, Mn: 1.57 wt%, and the remainder is iron and impurities. It was purchased from Jinzhou Haixin Metal Materials Co., Ltd.
[0027] The ferroniobium alloy in this application has a particle size of 5 to 30 mm, and its main components are Nb: 65.92 wt%, Si: 1.97 wt%, C: 0.12 wt%, Al: 0.94 wt%, S: 0.018 wt%, P: 0.258 wt%, with the remainder being iron and impurities. It was purchased from Beijing High-Tech New Materials Technology Co., Ltd.
[0028] The vanadium nitrogen alloy in this application has a particle size of 5-10 mm, and its main components are V: 77.69 wt%, S: 0.075 wt%, C: 5.53 wt%, N: 14.1 wt%, P: 0.045 wt%, and the remainder are iron and impurities. It was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.
[0029] Nickel in this application is added as nickel plate, which has a nickel content of 99.9 wt%, the remainder being iron and impurity elements, purchased from Jiangsu Guoyan Special Steel Co., Ltd.
[0030] The aluminum in this application is added as aluminum particles, with an aluminum content of 99.5 wt%, the remainder being iron and impurity elements, purchased from Xuchang Shengtong Metal Materials Co., Ltd. Example 1
[0031] The present invention relates to a composition containing 0.07% by weight of C, 1.35% by weight of Si, 0.45% by weight of Mn, 1.35% by weight of Cr, 0.05% by weight of Ni, 0.001% by weight of O, 0.001% by weight of S, 0.01% by weight of Ti, 0.01% by weight of Al, 0.005% by weight of V, and 0.005% by weight of Nb, with the remainder being Fe and unavoidable impurities, Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=3, the contents of Si and Cr satisfy Si / Cr=1, and the contents of Ti and Al satisfy Ti+Al=0.02%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1610°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 3.3:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 3.3:0.05:0.1:0.05:1, the amount of nickel plate added was 60 kg, the amount of aluminum particles added was 25 kg, and the amount of silicon manganese alloy added was 750 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1550℃ for 40 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 3 m / min. The cross-sectional size of the resulting continuous cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1190°C over 100 minutes, and then rolled at a rough rolling temperature of 1035°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 14 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 920°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 2 m / min. Example 2
[0032] The present invention relates to a composition containing 0.1% by weight of C, 1.5% by weight of Si, 0.55% by weight of Mn, 1.5% by weight of Cr, 0.5% by weight of Ni, 0.003% by weight of O, 0.0025% by weight of S, 0.05% by weight of Ti, 0.05% by weight of Al, 0.015% by weight of V, and 0.015% by weight of Nb, with the remainder being Fe and unavoidable impurities; Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=2.7, the contents of Si and Cr satisfy Si / Cr=1, and the contents of Ti and Al satisfy Ti+Al=0.1%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1630°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 3.1:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 3.1:0.15:0.5:0.15:1, the amount of nickel plate added was 600kg, the amount of aluminum particles added was 130kg, and the amount of silicon manganese alloy added was 920kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1555℃ for 40 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. During continuous casting, the drawing speed is set to 2.7 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1210°C over 110 minutes, and then rolled at a rough rolling temperature of 1025°C and a finish rolling temperature of 1010°C to obtain a rebar with a diameter of 25 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 930°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.5 m / min. Example 3
[0033] The present invention is directed to a composition including 0.12% by weight of C, 1.65% by weight of Si, 0.75% by weight of Mn, 1.75% by weight of Cr, 1% by weight of Ni, 0.005% by weight of O, 0.0035% by weight of S, 0.075% by weight of Ti, 0.075% by weight of Al, 0.03% by weight of V, and 0.03% by weight of Nb, with the remainder being Fe and unavoidable impurities; Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=2.2, the contents of Si and Cr satisfy Si / Cr=0.94, and the contents of Ti and Al satisfy Ti+Al=0.15%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1635°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 2.5:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 2.7:0.3:0.8:0.3:1, the amount of nickel plate added was 1200kg, the amount of aluminum particles added was 250kg, and the amount of silicon manganese alloy added was 1250kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1515℃ for 50 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 2.6 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1210°C over 110 minutes, and then rolled at a rough rolling temperature of 1025°C and a finish rolling temperature of 1010°C to obtain a rebar with a diameter of 32 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 880°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.1 m / min. Example 4
[0034] The present invention relates to a composition containing 0.05% by weight of C, 1.2% by weight of Si, 0.4% by weight of Mn, 0.85% by weight of Cr, 0.05% by weight of Ni, 0.001% by weight of O, 0.001% by weight of S, 0.005% by weight of Ti, 0.025% by weight of Al, 0.005% by weight of V, and 0.005% by weight of Nb, with the remainder being Fe and unavoidable impurities; Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=3, the contents of Si and Cr satisfy Si / Cr=1.41, and the contents of Ti and Al satisfy Ti+Al=0.03%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1600°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 3.5:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 2.5:0.05:0.05:0.05:1, the amount of nickel plate added was 60 kg, the amount of aluminum particles added was 70 kg, and the amount of silicon manganese alloy added was 670 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1540℃ for 30 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 3 m / min. The cross-sectional size of the resulting continuous cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1230°C over 120 minutes, and then rolled at a rough rolling temperature of 1070°C and a finish rolling temperature of 1050°C to obtain a rebar with a diameter of 28 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 920°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.2 m / min. Example 5
[0035] The present invention is directed to a composition including 0.15% by weight of C, 1.8% by weight of Si, 0.9% by weight of Mn, 2% by weight of Cr, 1% by weight of Ni, 0.005% by weight of O, 0.0035% by weight of S, 0.1% by weight of Ti, 0.1% by weight of Al, 0.03% by weight of V, and 0.03% by weight of Nb, with the remainder being Fe and unavoidable impurities; Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=2, the contents of Si and Cr satisfy Si / Cr=0.9, and the contents of Ti and Al satisfy Ti+Al=0.2%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1639°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 2:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 2.5:0.3:1.2:0.3:1, the amount of nickel plate added was 1200 kg, the amount of aluminum particles added was 30 kg, and the amount of silicon manganese alloy added was 1500 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1560℃ for 45 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 2.5 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1150°C over 90 minutes, and then rolled at a rough rolling temperature of 1000°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 10 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 820°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 2.2 m / min. Example 6
[0036] The present invention relates to a composition containing 0.05% by weight of C, 1.05% by weight of Si, 0.3% by weight of Mn, 0.8% by weight of Cr, 0.05% by weight of Ni, 0.001% by weight of O, 0.001% by weight of S, 0.025% by weight of Ti, 0.005% by weight of Al, 0.005% by weight of V, 0.005% by weight of Nb, and the remainder being Fe and unavoidable impurities, Here, there is provided a corrosion-resistant alloy rebar in which the Si and Mn contents satisfy Si / Mn=3.5, the Si and Cr contents satisfy Si / Cr=1.31, and the Ti and Al contents satisfy Ti+Al=0.03%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1650°C to obtain molten steel. The mass ratio of the ferrochrome alloy to the silicon manganese alloy was 3.8:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 2.6:0.05:0.3:0.05:1, the amount of nickel plate added was 60 kg, the amount of aluminum particles added was 20 kg, and the amount of silicon manganese alloy added was 500 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1550℃ for 35 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 2.5 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1180°C over 100 minutes, and then rolled at a rough rolling temperature of 1020°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 18 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 860°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.4 m / min. Example 7
[0037] The present invention relates to a composition containing 0.25% by weight of C, 2% by weight of Si, 1% by weight of Mn, 2.5% by weight of Cr, 1% by weight of Ni, 0.005% by weight of O, 0.0035% by weight of S, 0.1% by weight of Ti, 0.1% by weight of Al, 0.03% by weight of V, and 0.03% by weight of Nb, with the remainder being Fe and unavoidable impurities; Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=2, the contents of Si and Cr satisfy Si / Cr=0.8, and the contents of Ti and Al satisfy Ti+Al=0.2%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1600°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 2.2:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 3:0.3:1.1:0.3:1, the amount of nickel plate added was 1200kg, the amount of aluminum particles added was 250kg, and the amount of silicon manganese alloy added was 1665kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1540℃ for 40 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. During continuous casting, the drawing speed is set to 2.7 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1250°C over 120 minutes, and then rolled at a rough rolling temperature of 1120°C and a finish rolling temperature of 1100°C to obtain a rebar with a diameter of 22 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 1000°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.45 m / min. Example 8
[0038] The present invention relates to a composition containing 0.1% by weight of C, 1.05% by weight of Si, 0.35% by weight of Mn, 0.75% by weight of Cr, 0.15% by weight of Ni, 0.0025% by weight of O, 0.0025% by weight of S, 0.03% by weight of Ti, 0.03% by weight of Al, 0.01% by weight of V, 0.01% by weight of Nb, and the remainder being Fe and unavoidable impurities, Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=3, the contents of Si and Cr satisfy Si / Cr=1.4, and the contents of Ti and Al satisfy Ti+Al=0.06%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1620°C to obtain molten steel. The mass ratio of the ferrochrome alloy to the silicon manganese alloy was 3.3:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 2.1:0.1:0.3:0.1:1, the amount of nickel plate added was 180 kg, the amount of aluminum particles added was 250 kg, and the amount of silicon manganese alloy added was 585 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1545℃ for 40 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 3.5 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1200°C over 100 minutes, and then rolled at a rough rolling temperature of 1020°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 16 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 880°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.6 m / min. Example 9
[0039] The present invention relates to a composition containing 0.25% by weight of C, 1.5% by weight of Si, 0.3% by weight of Mn, 1% by weight of Cr, 0.05% by weight of Ni, 0.001% by weight of O, 0.001% by weight of S, 0.1% by weight of Ti, 0.05% by weight of Al, 0.005% by weight of V, 0.005% by weight of Nb, and the remainder being Fe and unavoidable impurities, Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=5, the contents of Si and Cr satisfy Si / Cr=1.5, and the contents of Ti and Al satisfy Ti+Al=0.15%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1650°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 5:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 3.3:0.05:1.1:0.05:1, the amount of nickel plate added was 60 kg, the amount of aluminum particles added was 125 kg, and the amount of silicon manganese alloy added was 500 kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1560℃ for 60 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. During continuous casting, the drawing speed is set to 3.1 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1230°C over 120 minutes, and then rolled at a rough rolling temperature of 1060°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 22 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 1000°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.45 m / min. Example 10
[0040] The present invention relates to a composition containing 0.05% by weight of C, 1.86% by weight of Si, 0.93% by weight of Mn, 2.48% by weight of Cr, 1% by weight of Ni, 0.005% by weight of O, 0.0035% by weight of S, 0.005% by weight of Ti, 0.015% by weight of Al, 0.03% by weight of V, 0.03% by weight of Nb, and the remainder being Fe and unavoidable impurities, Here, there is provided a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=2, the contents of Si and Cr satisfy Si / Cr=0.75, and the contents of Ti and Al satisfy Ti+Al=0.02%. The manufacturing method of the above corrosion-resistant alloy rebar includes the following steps. Smelting process: Ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, ferrosilicon alloy, silicon manganese alloy, nickel plate, and aluminum particles were smelted at 1600°C to obtain molten steel. The mass ratio of the ferrosilicon alloy to the silicon manganese alloy was 2.2:1, the mass ratio of the ferrochrome alloy, ferroniobium alloy, ferrotitanium alloy, vanadium nitrogen alloy, and silicon manganese alloy was 3.0:0.3:0.2:0.3:1, the amount of nickel plate added was 1200kg, the amount of aluminum particles added was 325kg, and the amount of silicon manganese alloy added was 1550kg. Refining process: Argon gas was introduced into the molten steel, and then it was refined at 1540℃ for 30 minutes. Continuous casting process: The refined molten steel is cast into a continuous cast billet using a continuous casting machine. The drawing speed during continuous casting is set to 2.8 m / min. The cross-sectional size of the resulting continuously cast billet is 140 mm. 2 It is. Rolling process: The continuous cast billet obtained in the continuous casting process was heated to 1180°C over 90 minutes, and then rolled at a rough rolling temperature of 1020°C and a finish rolling temperature of 1000°C to obtain a rebar with a diameter of 22 mm. Cooling process: The reinforcing bar obtained in the rolling process was cooled to 950°C, then transferred to a cooling bed and cooled, followed by air cooling, with the conveying speed of the cooling bed being 1.45 m / min. Comparative Example 1
[0041] The present application includes C: 0.1 weight%, Si: 2.15 weight%, Mn: 0.3 weight%, Cr: 1 weight%, Ni: 0.05 weight%, O: 0.001 weight%, S: 0.0035 weight%, Ti: 0.08 weight%, Al: 0.07 weight%, V: 0.005 weight%, Nb: 0.005 weight%, The present invention provides a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=7.17, the contents of Si and Cr satisfy Si / Cr=2.15, and the contents of Ti and Al satisfy Ti+Al=0.15%. In the manufacturing method of the above corrosion-resistant alloy rebar, compared with Example 8, the only difference is that in the smelting step, the mass ratio of the ferro-silicon alloy to the silicon-manganese alloy is 6.5:1, the mass ratio of the ferro-chrome alloy, the ferro-niobium alloy, the ferro-titanium alloy, the vanadium-nitrogen alloy, and the silicon-manganese alloy is 3.6:0.05:0.8:0.05:1, the amount of nickel plate added is 60 kg, the amount of aluminum particles added is 180 kg, and the amount of silicon-manganese alloy added is 500 kg. Comparative Example 2
[0042] The present application includes C: 0.1 weight%, Si: 1.5 weight%, Mn: 1.65 weight%, Cr: 1 weight%, Ni: 0.05 weight%, O: 0.001 weight%, S: 0.0035 weight%, Ti: 0.08 weight%, Al: 0.07 weight%, V: 0.005 weight%, Nb: 0.005 weight%, The present invention provides a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=0.91, the contents of Si and Cr satisfy Si / Cr=1.5, and the contents of Ti and Al satisfy Ti+Al=0.15%. In the manufacturing method of the above corrosion-resistant alloy rebar, compared with Example 8, the only difference is that in the smelting step, the mass ratio of the ferro-silicon alloy to the silicon-manganese alloy is 0.8:1, the mass ratio of the ferro-chrome alloy, the ferro-niobium alloy, the ferro-titanium alloy, the vanadium-nitrogen alloy, and the silicon-manganese alloy is 0.6:0.05:0.8:0.05:1, the amount of nickel plate added is 60 kg, the amount of aluminum particles added is 180 kg, and the amount of silicon-manganese alloy added is 2750 kg. Comparative Example 3
[0043] The present application includes C: 0.1 weight%, Si: 1.5 weight%, Mn: 0.3 weight%, Cr: 3 weight%, Ni: 0.05 weight%, O: 0.001 weight%, S: 0.0035 weight%, Ti: 0.08 weight%, Al: 0.07 weight%, V: 0.005 weight%, Nb: 0.005 weight%, The present invention provides a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=5, the contents of Si and Cr satisfy Si / Cr=0.5, and the contents of Ti and Al satisfy Ti+Al=0.15%. In the manufacturing method of the above corrosion-resistant alloy rebar, compared with Example 8, the only difference is that in the smelting step, the mass ratio of ferro-silicon alloy to silicon-manganese alloy is 4.5:1, the mass ratio of ferro-chrome alloy, ferro-niobium alloy, ferro-titanium alloy, vanadium-nitrogen alloy, and silicon-manganese alloy is 10:0.05:0.8:0.05:1, the amount of nickel plate added is 60 kg, the amount of aluminum particles added is 180 kg, and the amount of silicon-manganese alloy added is 500 kg. Comparative Example 4
[0044] The present application includes C: 0.1 weight%, Si: 1.5 weight%, Mn: 0.3 weight%, Cr: 1 weight%, Ni: 0.05 weight%, O: 0.001 weight%, S: 0.0035 weight%, Ti: 0.15 weight%, Al: 0.07 weight%, V: 0.005 weight%, Nb: 0.005 weight%, The present invention provides a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=5, the contents of Si and Cr satisfy Si / Cr=1.5, and the contents of Ti and Al satisfy Ti+Al=0.22%. In the manufacturing method of the above corrosion-resistant alloy rebar, compared with Example 8, the only difference is that in the smelting step, the mass ratio of ferro-silicon alloy to silicon-manganese alloy is 4.5:1, the mass ratio of ferro-chrome alloy, ferro-niobium alloy, ferro-titanium alloy, vanadium-nitrogen alloy, and silicon-manganese alloy is 3.3:0.05:1.55:0.05:1, the amount of nickel plate added is 60 kg, the amount of aluminum particles added is 180 kg, and the amount of silicon-manganese alloy added is 500 kg. Comparative Example 5
[0045] The present application includes C: 0.1 weight%, Si: 1.5 weight%, Mn: 0.3 weight%, Cr: 1 weight%, Ni: 0.05 weight%, O: 0.001 weight%, S: 0.0035 weight%, Ti: 0.08 weight%, Al: 0.15 weight%, V: 0.005 weight%, Nb: 0.005 weight%, The present invention provides a corrosion-resistant alloy rebar in which the contents of Si and Mn satisfy Si / Mn=5, the contents of Si and Cr satisfy Si / Cr=1.5, and the contents of Ti and Al satisfy Ti+Al=0.22%. In the manufacturing method of the above corrosion-resistant alloy rebar, compared with Example 8, the only difference is that in the smelting step, the mass ratio of the ferro-silicon alloy to the silicon-manganese alloy is 4.5:1, the mass ratio of the ferro-chrome alloy, the ferro-niobium alloy, the ferro-titanium alloy, the vanadium-nitrogen alloy, and the silicon-manganese alloy is 3.3:0.05:0.8:0.05:1, the amount of nickel plate added is 60 kg, the amount of aluminum particles added is 380 kg, and the amount of silicon-manganese alloy added is 500 kg. Test Example 1
[0046] The mechanical properties of the corrosion-resistant alloy rebars manufactured in the examples and comparative examples were tested according to the national standard GB / T228.1-2010 Metallic Material Tensile Test Part 1: Room Temperature Test Method, and the tensile strength-yield strength ratio (i.e., tensile strength / yield strength) was calculated. The test results are shown in Table 1.
[0047] [Table 1] As can be seen from the data in Table 1, in this application, only when the conditions of the proportion of each element are met, the yield strength ≧ 430 MPa, the elongation after fracture ≧ 20.5%, the tensile strength to yield strength ratio ≧ 1.26, and the maximum total elongation ≧ 10.6% can be ensured, and even when the Mo element is not added to the formula and the Cr element content is significantly reduced, excellent mechanical properties can be obtained. Test Example 2
[0048] Using a Zeiss optical microscope, the structure types of the corrosion-resistant alloy rebars manufactured in the examples and comparative examples were observed at 200 times magnification, and the volume fraction of ferrite therein was calculated. The test results are shown in Table 2. Test Example 3
[0049] Using an electrochemical workstation equipped with a working electrode, a reference electrode, and a counter electrode system, the critical chloride ion concentration value of the destruction of the passive film on the surface of the corrosion-resistant alloy rebar manufactured in the examples and comparative examples was tested, and compared with the HRB400 model rebar, the improvement factor of the critical chloride ion concentration value was calculated. The specific test method is as follows: The test sample was immersed in a saturated sodium hydroxide solution for 48 h, and then placed in the electrochemical workstation and used as the working electrode. Every 24 h, 0.01 mol / L sodium chloride solution was added to the solution in the electrochemical workstation, and the voltage / current-chlorine ion concentration curve was tested. When the current or voltage changes suddenly, the corresponding chloride ion concentration value becomes the critical chloride ion concentration value. The calculation formula is improvement factor = critical chloride ion concentration value of corrosion-resistant alloy rebar / critical chloride ion concentration value of HRB400 rebar. The test results are shown in Table 2. The components and composition ratios of the reinforcing bars of the above HRB400 model are C: 0.24%, Si: 0.40%, Mn: 1.40%, V: 0.025%, P≦0.04%, S≦0.04%. Test Example 4
[0050] The corrosion resistance of the corrosion-resistant alloy rebars manufactured in the examples and comparative examples was tested for chlorine salt corrosion resistance, and compared with the HRB400 model rebar to calculate the improvement factor of the corrosion resistance. The specific test method is as follows. One end of the corrosion-resistant alloy rebars of each example and comparative example was cut to a length of 100 mm, and a lathe was used to make a test piece with a diameter of 8 mm. The test piece was placed in a corrosion solution at a temperature of 35°C and a humidity of 80% to carry out a salt spray corrosion test. The corrosion solution for the test was a sodium chloride solution with a chloride salt concentration of 5 wt%, its pH value was 7.0, and the test time was 14 days. The weight of the test sample before and after corrosion was tested with an electronic microbalance. The calculation formula is improvement factor = weight change value before and after corrosion of corrosion-resistant alloy rebar / weight change value before and after corrosion of HRB400. The test results are shown in Table 2. The components and composition ratios of the reinforcing bars of the above HRB400 model are C: 0.24%, Si: 0.40%, Mn: 1.40%, V: 0.025%, P≦0.04%, S≦0.04%.
[0051] [Table 2] JPEG2025506561000003.jpg116138
[0052] From the results in Table 2 above, it can be seen that in the corrosion-resistant alloy rebar of the present invention, the proportion of ferrite in the microstructure type reaches 53 to 73%, and compared with HRB400, the critical chloride ion concentration value is improved by more than 2.1 times, and the chlorine salt corrosion resistance is improved by more than 2.7 times, and the overall performance is significantly improved.
[0053] From the data in Tables 1 and 2, it is clear that the composition ratio of the present application is able to achieve both mechanical properties and corrosion resistance, and has excellent overall performance. In addition, the composition formulation of the present application does not contain Mo element, and the content of Cr element is significantly reduced, which significantly reduces costs.
[0054] Obviously, the above examples are merely examples for clear explanation, and do not limit the embodiments. Those skilled in the art may make other different changes or modifications based on the above description. It is not necessary and impossible to comprehensively cover all the embodiments here. And, obvious changes or modifications derived therefrom still fall within the scope of protection of the present invention.
Claims
1. %. The alloy contains 0.05-0.25 wt. % C, 1.05-2 wt. % Si, 0.3-1.5 wt. % Mn, 0.5-2.5 wt. % Cr, 0.05-1 wt. % Ni, 0.001-0.005 wt. % O, 0.001-0.0035 wt. % S, 0.005-0.1 wt. % Ti, 0.005-0.1 wt. % Al, 0.005-0.03 wt. % V, and 0.005-0.03 wt. % Nb, with the remainder being Fe and unavoidable impurities. The Si and Mn contents satisfy 2≦Si / Mn≦5, the Si and Cr contents satisfy 0.75≦Si / Cr≦1.5, and the Ti and Al contents satisfy 0.02%≦Ti+Al≦0.2%.
2. The Si content is 1.2 to 1.8%, And / or, the Mn content is 0.4 to 1%, And / or, the Cr content is 0.85 to 2%.
3. The Si content is 1.35 to 1.65%, And / or, the Mn content is 0.45 to 0.75%, And / or, the Cr content is 1.35 to 1.75%.
4. The corrosion-resistant alloy reinforcing bar according to claim 1, characterized in that the C content is 0.05 to 0.15%.
5. The corrosion-resistant alloy reinforcing bar according to claim 4, characterized in that the C content is 0.07 to 0.12%.
6. The Ti content is 0.01 to 0.075%, And / or, the content of Al is 0.01 to 0.075%.
7. The method for producing the corrosion-resistant alloy reinforcing bar according to any one of claims 1 to 6, characterized in that it comprises the steps of smelting, refining, continuous casting, rolling and cooling, which are carried out in sequence.
8. The manufacturing method according to claim 7, characterized in that the raw materials for manufacturing the corrosion-resistant alloy rebar include ferrosilicon alloy and silicon manganese alloy, and the mass ratio of the ferrosilicon alloy to the silicon manganese alloy is (2-5):
1.
9. In the continuous casting step, the drawing speed is 2.5 to 3.5 m / min; And / or, in the cooling step, the temperature of the reinforcing bar transferred to the cooling bed is 820°C to 1000°C; And / or, the rolling step includes a step of heating the continuous cast billet and performing rough rolling and finish rolling.
10. The method according to claim 9, wherein the temperature for heating the continuous cast billet is 1150 to 1250°C, the rough rolling temperature is 1000 to 1120°C, and the finish rolling temperature is 1000°C or higher.
Citation Information
Patent Citations
Low-alloy high-strength corrosion-resistant steel bar and preparation method thereof
CN112226693A
Production of high strength and low yield ratio bar steel for reinforcing bar
JP1994136441A
Production of steel for high strength and low yield ratio reinforcing bar
JP1994228635A
High-strength steel and high-strength bolt with excellent resistance to delayed fracture, and manufacturing method therefor
WO2011111872A1